# SOLUTION: How do I solve: y=x^3-2x^2+x-1 y=-x^2+3x-1 I substituted y=-x^2+3x-1 -x^2+3x-1=x^3-2x^2+x-1 0=x^3-x^2-2x Not sure what to do next

Algebra ->  Algebra  -> Coordinate Systems and Linear Equations  -> Lessons -> SOLUTION: How do I solve: y=x^3-2x^2+x-1 y=-x^2+3x-1 I substituted y=-x^2+3x-1 -x^2+3x-1=x^3-2x^2+x-1 0=x^3-x^2-2x Not sure what to do next      Log On

 Ad: You enter your algebra equation or inequality - Algebrator solves it step-by-step while providing clear explanations. Free on-line demo . Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Linear Solvers Practice Answers archive Word Problems Lessons In depth

 Click here to see ALL problems on Linear-systems Question 568770: How do I solve: y=x^3-2x^2+x-1 y=-x^2+3x-1 I substituted y=-x^2+3x-1 -x^2+3x-1=x^3-2x^2+x-1 0=x^3-x^2-2x Not sure what to do nextAnswer by josmiceli(9664)   (Show Source): You can put this solution on YOUR website! By substitution: Add to both sides Factor out The solutions are: You can verify these by plugging them back into